Empirical Evidence of Target Leverage, Adjustment Costs and Adjustment Speed of Non-Financial Firms in Selected African Countries - Etudaiye-Muhtar, Oyebola Fatima; Ahmad, Rubi (International Journal of Economics and Financial Issues, 2015)
The issue of target leverage for corporate firms in developing countries has received little attention in extant literature, especially countries in Africa. Given the imperfection that exists in African financial markets that may limit firms access to external capital, this study investigates dynamic adjustment towards a target debt ratio. In addition, the study used a dynamic panel data estimation technique to determine adjustment costs and speed of adjustment in non-financial firms in selected African countries over the period 2003 to 2012. The study finds that the firms make dynamic adjustment to a target leverage with low adjustment costs and relatively fast speed of adjustment. Keywords: capital structure; target leverage; adjustment costs JEL Classification: G32